2018
DOI: 10.1002/arp.1731
|View full text |Cite
|
Sign up to set email alerts
|

Using deep neural networks on airborne laser scanning data: Results from a case study of semi‐automatic mapping of archaeological topography on Arran, Scotland

Abstract: This article presents results of a case study within a project that seeks to develop heavily automated analysis of digital topographic data to extract archaeological information and to expedite large area mapping. Drawing on developments in computer vision and machine learning, this has the potential to fundamentally recast the capacity of archaeological prospection to cover large areas and deal with mass data, breaking a dependency on human resource. Without such developments, the potential of the vast amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 23 publications
1
106
0
Order By: Relevance
“…This means that it is still necessary to intervene manually, which requires a lot of time, manpower and material resources [53][54][55]. With the rapid development of image and signal processing and computer vision, several (semi-) automatic approaches have also been designed for and applied to archaeological research [56][57][58][59][60]. For instance, Lasaponara et al [55] designed a classification-based semi-automatic approach for identifying four buried farm objects at the Hierapolis site; the identification results were then qualitatively evaluated by combining visual interpretation with the GPR survey data.…”
Section: Archaeological Remote Sensingmentioning
confidence: 99%
“…This means that it is still necessary to intervene manually, which requires a lot of time, manpower and material resources [53][54][55]. With the rapid development of image and signal processing and computer vision, several (semi-) automatic approaches have also been designed for and applied to archaeological research [56][57][58][59][60]. For instance, Lasaponara et al [55] designed a classification-based semi-automatic approach for identifying four buried farm objects at the Hierapolis site; the identification results were then qualitatively evaluated by combining visual interpretation with the GPR survey data.…”
Section: Archaeological Remote Sensingmentioning
confidence: 99%
“…Automatic feature detection approaches for archaeology are a rapidly and fast developing field in archaeological prospection [60][61][62]. Recent studies have demonstrated machine learning methods for detecting a wide variety of features, including burial mounds, charcoal kilns, buildings, and field systems [10,[63][64][65][66].…”
Section: Evaluating Our Approachmentioning
confidence: 99%
“…Our automatic approach is, hence, adaptable to search for a wide variety of circular surface structures where digital elevation models (DEMs) are available. Such future studies could focus on common geomorphological features such as meandering rivers, coastal erosion scars, and glacial landforms [10,42,82], but also remote mapping of impact craters from meteors [57], bomb craters [83], and center pivot irrigation [84]. It may be even applicable on extra-terrestrial bodies [85].…”
Section: Detection Of the Natural Surface Featurementioning
confidence: 99%
See 1 more Smart Citation
“…The main interest however, has been focused mainly on the analysis of archaeological features from airborne laser scanning (ALS) and satellite data. Such applications have been summarized by Trier, Cowley, and Waldeland (), Opitz and Herrmann (), Davis (), and Davis, Lipo, and Sanger (); and the recent studies of Verschoof‐van, der Vaart, and Lambers (), Meyer, Pfeffer, and Jürgens (), and Lambers, Verschoof‐van der Vaart, and Bourgeois (). Automated analysis is also considered to be an important approach for ground‐based geophysical surveys.…”
Section: Introductionmentioning
confidence: 99%